Communication Disorders and Persons with Developmental Disabilities. - Cascella, Paul W. (2002)
Keywords: dept.cmd; faculty_collection; sabbatical_report

Clinical efficacy of electrophysiologic measures in APD management programs - Jirsa, R.E. (Seminars in Hearing, 2002)
Determining the relative efficacy of various intervention programs for auditory processing disorders (APD) is a major goal in the field of rehabilitative audiology. Currently, because of their widespread availability, the most commonly used measuring tools to assess the central auditory system have been behaviorally based. Such measures do have notable disadvantages in that they may be influenced by a number of extraneous variables that may impede, or at least influence, efficacy measures. Electrophysiologic measures offer unique advantages not available from the behavioral measures. A significant amount of research has been completed offering compelling evidence relative to the clinical utility of a number of these electrophysiologic measures, including the maximum length sequences-auditory brainstem response, the middle latency response, the obligatory long latency responses, and the MMN and P3 event-related potentials. This article will review the current research related to electrophyiologic measures and present a rationale for including them in the management program.
11 citations (Crossref) [2023-10-31]
Keywords: Clinical efficacy; Electrophysiology; Middle latency response; Mismatch negativity; P3 event-related potential; Speech perception; auditory nervous system; clinical practice; dept.cmd; diagnostic accuracy; diagnostic procedure; electrophysiology; event related potential; evoked auditory response; human; middle latency response; mismatch negativity; perception deafness; review; speech perception

Executive function ability in persons with aphasia - Purdy, M. (Aphasiology, 2002)
Background: There is an increasing recognition that the communication problems one observes in persons with aphasia extend beyond verbal deficits and that the myriad of symptoms observed are not solely due to a faulty linguistic system. Rather, there exists a coalition of causal elements resulting in a wide range of communicative deficits. There is some preliminary evidence suggesting that communicative success of clients with aphasia may depend on the integrity of executive function skills. Executive functions are called into play when an individual is involved in a complex, novel activity. They allow us to plan, sequence, organise, and monitor goal-directed activities in a flexible manner as demanded by situational and environmental changes. When linguistic skills are impaired, individuals need to rely on other cognitive skills in order to communicate. Aims: The purpose of this study was to explore executive functioning ability in persons with aphasia. Methods & procedures: A total of 15 individuals with aphasia and 12 healthy control subjects participated in this study. Three dimensions of performance were examined (accuracy, speed, and efficiency) in the context of neuropsychological tests designed to examine cognitive flexibility and goal-directed planning (Wisconsin Card Sorting Test, Porteus Maze Test, Tower of London, and Tower of Hanoi). Outcomes & results: Results indicated that the two groups performed with similar levels of accuracy on two of the four tests. However, significant differences were found on all speed and efficiency variables, suggesting decreased executive functioning skills in the group of individuals with aphasia. Conclusions: It is important to consider executive functioning ability in clients with aphasia and attempt to determine the influence of executive function skill on communicative performance. Understanding the cognitive abilities as well as the linguistic abilities of these clients may ultimately help clinicians determine which patients are better candidates for intervention as well as which treatment approaches would be most efficient and beneficial.
108 citations (Crossref) [2023-10-31]
Keywords: Wisconsin card sorting test; accuracy; adult; aged; aphasia; article; clinical article; cognition; communication disorder; comparative study; controlled study; dept.cmd; human; interpersonal communication; language ability; linguistics; maze test; mental function; mental performance; neuropsychological test; peer-reviewed; planning; skill; treatment planning

Script knowledge following stroke - Purdy, M.H. (Journal of Medical Speech-Language Pathology, 2002)
This study examined script knowledge in 20 subjects who sustained a stroke (10 with left hemisphere brain damage and aphasia and 10 with right hemisphere brain damage) and 10 neurologically normal subjects. Script knowledge was examined via performance on three tasks: procedural sequencing, procedure production, and procedural discourse. Neurologically normal subjects performed all tasks accurately, and all subjects in the stroke group completed at least one of the three tasks for each script accurately, suggesting that script knowledge was preserved in this mildly brain-damaged population. However, significant differences were obtained between the neurologically normal and stroke groups when overall performance was examined. These findings suggest that additional cognitive processes influence task performance. Implications of these findings are discussed.
Keywords: adult; aged; aphasia; article; clinical article; controlled study; dept.cmd; female; human; information processing; language ability; left hemisphere; male; priority journal; right hemisphere; stroke; task performance; ⛔ No DOI found